A description of the Elevation sensitive Oblique Incidence Sounder Experiment (ELOISE). Issue 10 (15th November 2019) - Gardiner-Garden, R.; Cervera, M.; Debnam, R.; Harris, T.; Heitmann, A.; Holdsworth, D.; Netherway, D.; Northey, B.; Pederick, L.; Praschifka, J.; Quinn, A.; Turley, M.; et al.
Abstract: The Elevation sensitive Oblique Incidence Sounder Experiment (ELOISE) was an extensive experiment undertaken by the Defence Science and Technology (DST) Group that focused on collecting ionospheric sensor data from multiple overlapping ionospheric paths in the Australian region in order to improve understanding of the characteristics of ionospheric variability and its effect on HF radio propagation. The experiment ran from July to October 2015 and included a period of three weeks of increased sample density and three days of dedicated over-the-horizon (OTH) radar operations. It was anticipated that ELOISE would sample a wide range of environmental conditions and present an opportunity to characterise periods of "normal variability" and periods of "exceptional variability" in the ionosphere. This report is a general description of the aims of this experiment and the types of data collected. Particular interest focused on observing and measuring variability in ionospheric electron density gradients and their effect on oblique HF propagation. To this end, ELOISE established a pair of two dimensional HF receiver arrays to directly measure the oblique angle of arrival (AoA) on many overlapping oblique paths. ELOISE also established a dense sub-network of spatially separated quasi-vertical incidence soundings in the vicinity of Alice Springs in central Australia. This enabled a comparison of gradients observed in a dense network of vertical sounders with gradient effects observed in oblique propagation passing overhead. Several additional ionospheric observing systems were also used to give complementary pictures of the fine scale characteristics of ionospheric variability in the region. Plain Language Summary: This paper is an overview of the 2015 Elevation sensitive Oblique Incidence Sounder Experiment (ELOISE), an experiment designed to observe and characterise mid-latitude ionospheric disturbances in the Australian region and understand their impact on high frequency (HF) signal propagation. ELOISE involved the simultaneous operation of a large collection of ionospheric sounders enabling ionospheric variability to be characterised on a finely sampled large scale. Particular efforts were made to provide direct high fidelity measurements of the angle of arrival (AoA) on many oblique HF propagation paths. These direct AoA measurements imply horizontal electron density gradients that can be compared to ionospheric gradients estimated from conventional models of the ionosphere derived from the spatial network of sounder sites. The size and scope of the experiment are detailed in this paper and some preliminary results are presented.